The Relationship between Stress Level and the Incidence of Gastritis in Final Year Pharmacy Students at the University of Muhammadiyah Kudus - Nurul Shintya Dhevi; Endang Setyowati; Ulviani Yulia Husna (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to analyze the relationship between stress level and the incidence of gastritis among final-year Pharmacy students at the University of Muhammadiyah Kudus. It was hypothesized that higher stress levels would be associated with a greater incidence of gastritis. Research Method: This study employed a quantitative observational, cross-sectional design. The sample consisted of 103 seventh-semester Pharmacy students selected through purposive sampling. Stress level was measured using the Perceived Stress Scale-10 (PSS-10), while gastritis incidence was identified using a validated gastritis symptom questionnaire. Data were analyzed using univariate analysis and the Mann-Whitney test. Results and Discussion: Most respondents were 21 years old (63.1%), female (86.4%), and had no prior disease history (38.8%), although a history of stomach acid was common (32.0%). The majority experienced moderate stress (72.8%), and 20.4% experienced gastritis. Statistical analysis showed a significant relationship between stress level and gastritis incidence (p = 0.001), indicating that increasing stress level was associated with a higher risk of gastritis. Implications: These findings emphasize the importance of stress management and the promotion of digestive health among university students. Further research should include additional risk factors such as diet, sleep quality, and medication use.